THE SOCIALIZATION PROCESS OF PROSTITUTION:A CASE STUDY IN AN INDONESIAN REGENCY PRIMARY SOURCE OF PROSTITUTES - Koentjoro, - (Faculty of Psychology, Universitas Gadjah Mada, 1997)
This research sets out to understand socialization of prostitution in the rural areas of indonesia. This Â study seeks answers how and why socialization occurs in that community and factors which can be identified as contributing significantly to socialization of prostitution.